2021
DOI: 10.21468/scipostphys.10.3.058
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and flexible approach to simulate low-dimensional quantum lattice models with large local Hilbert spaces

Abstract: Quantum lattice models with large local Hilbert spaces emerge across various fields in quantum many-body physics. Problems such as the interplay between fermions and phonons, the BCS-BEC crossover of interacting bosons, or decoherence in quantum simulators have been extensively studied both theoretically and experimentally. In recent years, tensor network methods have become one of the most successful tools to treat such lattice systems numerically. Nevertheless, systems with large local Hilbert spaces remain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 67 publications
(146 reference statements)
0
34
0
Order By: Relevance
“…This regime is still clearly a candidate for other schemes to efficiently treat phonons, such as the one of Ref. [78]. In total, the limiting factor for our calculations in the metallic regime is the local bond dimension and obtaining a steady state.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This regime is still clearly a candidate for other schemes to efficiently treat phonons, such as the one of Ref. [78]. In total, the limiting factor for our calculations in the metallic regime is the local bond dimension and obtaining a steady state.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, in Ref. [78], Köhler et al suggested introducing bath sites, thus treating a doubled system but with a restored U(1) symmetry. The methodology was further applied to time-evolution calculations in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We overcome these issues by employing the newly developed method of projected-purification (PP) 33,52 . Within this approach we restore the U(1)-particle number conservation symmetry by doubling the size of the (phononic) system.…”
Section: Methodsmentioning
confidence: 99%
“…First, we compute the spectral density from ab-initio multireference quantum chemical calculations and determine the effect of the molecule's vibrational modes on the electronic overlap integrals to obtain an effective model, capturing the coupling between electronic states and vibrations. Employing the resulting microscopic model, we perform a simulation of the full post photo-excitation quantum dynamics using a novel method from tensor networks 33 . In particular, this method allows for the description of many bosonic degrees of freedom with a large number of internal states by dynamically selecting the relevant bosonic modes.…”
Section: Introductionmentioning
confidence: 99%
“…(3) (see [15]). Note that more general approaches exist to tackle this issue and have been applied to problems with fermionphonon coupling [16][17][18][19][20][21].…”
Section: Spins and Local Longitudinal Phonons Becomesmentioning
confidence: 99%